2011
DOI: 10.1111/j.1475-6765.2011.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

A psycho‐political profile of party activists and left‐wing and right‐wing extremists

Abstract: Profile of political party activists 2 A psycho-political profile of moderates and left-wing and right-wing extremists Abstract.The present study tests for differences among samples of activists from moderate and extreme political ideologies. Previous studies comparing ideological groups have been restricted to tests of betweengroup differences in the means of relevant political psychological variables, thereby neglecting eventual group differences in the variances, meanings and nomological networks of the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
4
32
0
1
Order By: Relevance
“…Second, because extreme right‐wing parties often focus on the threat that immigrants pose to the values and norms of the ingroup, one could expect that social‐cultural attitudes constitute the stronger correlate of support for such parties (see, Duckitt, ), an expectation that has not been substantiated. However, the present results attune well with research showing that extreme right‐wing party members seem to be primarily motivated by social dominance, especially as a basis of their perception of ethnic minorities (Ezekiel, ; Van Hiel, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, because extreme right‐wing parties often focus on the threat that immigrants pose to the values and norms of the ingroup, one could expect that social‐cultural attitudes constitute the stronger correlate of support for such parties (see, Duckitt, ), an expectation that has not been substantiated. However, the present results attune well with research showing that extreme right‐wing party members seem to be primarily motivated by social dominance, especially as a basis of their perception of ethnic minorities (Ezekiel, ; Van Hiel, ).…”
Section: Discussionsupporting
confidence: 89%
“…Racism is his tool” (p. 56). Among right‐wing extremists, interracial issues are primarily interpreted in terms of a continuing struggle for power, and their prejudice reflects antiegalitarian attitudes (Van Hiel, ). The present results thus extend these previous findings to the voters of extreme right‐wing parties.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the specific topics of interest examined in the English language literature in recent years have included: the development of social movements and collective action (Postmes & Brunsting, 2002;Sageman, 2004;Thomas, Smith, McGarty, & Postmes, 2010;Wojcieszak, 2009); collective identity formation (Baray, Postmes, & Jetton, 2009;Futrell, Simi, & Gottschalk, 2006;Futrell & Simi, 2004); the development of extremist beliefs (Adams & Roscigno, 2005;Ezekiel, 2002); extremist communication strategies (de Koster & Houtman, 2008;Gersenfeld, Grant, & Chiang, 2003;Glaser, Dixit, & Green, 2002;Levin, 2002;Schafer, 2002;Stromer-Galley, 2003;Weatherby & Scoggins, 2005/ 06); and the correlates of extremist beliefs (Green, Abelson, & Garnett, 1999;Janowitz & Marvick, 1953;McClosky & Chong, 1985;Pinderhughes, 1993;Schuman & Krysan, 1996;Sidanius, 1984Sidanius, , 1988Van Hiel, 2012;Van Hiel, Duriez, & Kossowska, 2006). Some of the specific topics of interest examined in the English language literature in recent years have included: the development of social movements and collective action (Postmes & Brunsting, 2002;Sageman, 2004;Thomas, Smith, McGarty, & Postmes, 2010;Wojcieszak, 2009); collective identity formation (Baray, Postmes, & Jetton, 2009;Futrell, Simi, & Gottschalk, 2006;Futrell & Simi, 2004); the development of extremist beliefs (Adams & Roscigno, 2005;Ezekiel, 2002); extremist communication strategies …”
Section: Overview Of Existing Researchmentioning
confidence: 99%
“…Like many other externally stigmatized communities, it is commonly reported that political extremists, both on the left and the right, are suspicious of researchers and their intentions (Blee & Creasap, 2010;Futrell, Simi, & Gottschalk, 2006;Jipson & Litton, 2000;McClosky & Chong, 1985;Van Hiel, 2012). Moreover, researchers sometimes are suspected of being informants for law enforcement agencies (Blee, 1999;Speckhard, 2009).…”
Section: Distrust Of Researchersmentioning
confidence: 99%
See 1 more Smart Citation